Prevalence and correlates of erectile dysfunction (ED) and treatment seeking for ED in Asian men: The Asian men's attitudes to life events and sexuality (MALES) study - Tan, H.M.; Low, W.Y.; Ng, C.J.; Chen, K.K.; Sugita, M.; Ishii, N.; Marumo, K.; Lee, S.W.; Fisher, W.; Sand, M. (2007)
Introduction. There have been limited multiregional studies in Asia examining the parameters of men's general and sexual health and quality of life in the general population vs. those in clinical cohorts of patients with erectile dysfunction (ED). Aims. The aims of the Asian Men's Attitudes to Life Events and Sexuality (Asian MALES) study were to investigate the prevalence of ED, associated health conditions, and ED treatment-seeking patterns in the general male population in five regions of Asia (China, Japan, Korea, Malaysia, and Taiwan). Main Outcome Measure. Standardized questionnaire previously used in a similar multiregional study and modified to ensure culturally appropriate content for Asia. Methods. Phase I of the study involved 10,934 adult men, aged 20-75 years, who were interviewed using the standardized questionnaire. Phase II of the study involved men with self-reported ED recruited from Phase I and via physician referral, invitations in general practitioner offices, and street interception (total Phase II sample, N = 1,209). Results. The overall prevalence of self-reported ED in the Phase I study population was 6.4. ED prevalence varied by region and significantly increased with age (P < 0.01). Men with ED reported significantly greater rates of comorbid illness (P < 0.0001) and a reduced quality of life (P = 0.0001), compared with men without ED. Phase II of the study revealed that fewer than half of men with self-reported ED had sought treatment for their problem. Men were more likely to seek help for erection difficulties from Western doctors than from traditional medicine practitioners (P = 0.0001). A man's partner/spouse was the most common influencer of treatment seeking in all regions except Malaysia. Conclusion. The findings confirm those of existing research on ED in both Asian and non-Asian males: ED is a prevalent condition; the prevalence of ED increases with age and is strongly associated with comorbid conditions; and the majority of men have never sought treatment for their condition. This study highlights a substantial need for the evaluation and treatment of ED in Asian men.